Use of the linear absorption coefficient for absolute comparison of plasma films in the mid-IR range - Gautier, T.; Carrasco, N.; Mahjoub, A.; Stefanovic, I.; Szopa, C.; Cernogora, G.; Hadamcik, E.; Winter, J. (Вопросы атомной науки и техники, 2013)
In this work, we present the mid-infrared analysis of analogues of Titan's aerosols produced in a radio frequency capacitively coupled plasma (RF-CCP). The influence of the gas mixture on aerosols spectra is also studied through the analysis of the carbonaceous bands of the spectra, and its Gaussian deconvolution. Представлен анализ в среднем инфракрасном диапазоне аналогов титановых аэрозолей, которые производятся в радиочастотных источниках плазмы с емкостной связью (РЧ-ЕСС). Также изучено влияние газовой смеси на спектры аэрозолей с помощью анализа углеродсодержащих полос спектра и ее гауссовой деконволюции (обратная свертка). Представлено аналіз у середньому інфрачервоному діапазоні аналогів титанових аерозолів, які проводяться в радіочастотних джерелах плазми з ємнісним зв'язком (РЧ-ЕСС). Також вивчено вплив газової суміші на спектри аерозолів за допомогою аналізу вуглецевмісних смуг спектра і її гауссової деконволюції (зворотня згортка).